Effects of Various Direct-acting Antivirals in the Quality of Life of Patients with Chronic Hepatitis C - Hatun ÖZTÜRK ÇERİK; Şaban ESEN; Betül ALTINTAŞ ÖNER; Merve ÇELİK; Tuğba ÖZDEMİR; İlkay BOZKURT; Esra TANYEL (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Chronic hepatitis C is an infectious disease known to affect people worldwide. The disease is characterized by both hepatic and extrahepatic manifestations that impair the patient’s overall quality of life (QoL). Potent and easy-to-use direct-acting antivirals (DAAs) have been recently introduced to treat chronic hepatitis C virus (HCV) infection. This study aimed to assess the QoL of patients with chronic HCV before and after DAAs treatment. Materials and Methods: The Liver Disease Symptom Index 2.0, Short Form-36 (SF-36), and Beck-Anxiety Inventory scale were administered before and at the end of the treatment to evaluate the QoL in patients who were initiated with sofosbuvir and ledipasvir (SOF/LED)±ribavirin (RBV) or ombitasvir, paritaprevir, ritonavir, and dasabuvir (PROD). In addition, another questionnaire was used to evaluate the treatment waiting period effects on the patients’ psychology. Results: A total of 46 patients receiving DAAs were included in the study, 22 of which received SOF/LED (group 1), four received SOF/LED+RBV (group 2), and 20 received PROD (group 3). At the end of the treatment, a significant improvement was observed in The Liver Disease Symptom Index 2.0 items including daytime sleepiness, effect of sleepiness on daily life, presence of depression, effect of depression on daily life, and fear of developing liver disease complication (p=0.002, p=0.035, p<0.001, p=0.039, and p=0.013, respectively). Among SF-36 parameters, a significant improvement was observed in physical functioning, physical role limitations, body pain, and vitality in groups 1 and 3 at the end of the treatment (p<0.001, p<0.001, p=0.001, and p<0.001). Direct-acting antivirals treatment has improved the Beck-Anxiety Inventory; however, when the RBV was added to the treatment, patients’ anxiety increased (p=0.0026). The effect of the waiting period for receiving HCV treatment on patients caused anxiety about disease progression and fear of developing cirrhosis. Conclusion: We conclude that DAAs contribute to improvement of the QoL of patients during and after HCV infection treatment.